The Effect of Family Management Style on Family Business Growth of UPI Tasikmalaya Students - Difa Nuresa; Falia Musi Ardani; Lulu Alya Rudiyanto; Indirwan Satria Purnama; Mira Nurfitriya; Azizah Fauziyah (Journal of Economics, Social, and Humanities, 2023)
Family businesses play an important role in a global economy that is full of challenges in achieving sustainable growth. One factor that continues to be studied in this context is the family management style that includes decision making, resource management, and business strategy development, so as to achieve sustainable growth. The purpose of this study was to determine the description of the influence of family management style and family business growth, and to determine the influence of family management style on family business growth. This research uses quantitative methods with a descriptive verification approach to collect and analyze data. Quantitative data were obtained through questionnaires with a population of 200 students and 48 samples of students whose families own and run businesses. The object of this research is family companies owned by the families of Entrepreneurship Students of Universitas Pendidikan Indonesia. The results of this study indicate that there is an influence of management style on the growth of the family business of students of the Universitas Pendidikan Indonesia Kampus Tasikmalaya. The results of this study provide valuable knowledge on how families can improve their business growth through the right management style.